OPTIMALISASI PERTUMBUHAN DAN PERKEMBANGAN BALITA DENGAN PENDIDIKAN KESEHATAN TENTANG SDIDTKB PADA ORANG TUA SISWA DI PAUD BUNNAYA ICBB YOGYAKARTA - Nining Sulistyawati; Annisa Hidayati (ABDIMAS Madani, 2019)
The development of basic abilities of children correlates with growth. The development of basic abilities has a fixed and sequential pattern. Therefore stimulation given to under five children in order to stimulate growth and development of children can be done according to their age. However, many parents still do not understand how to provide appropriate stimulation to their children at each stage of their development, as well as how to early detect problems with the growth and development of under five children. Based on interviews with parents of students at PAUD Bunnaya ICBB Yogyakarta, it was found that they did not understand about growth and development of under five children, especially how to stimulate their growth and development and how to detect problems regarding the growth and development. Method of this community service activities was in the form of health education. The participants of this activity were parents of students at PAUD Bunnaya ICBB Yogyakarta. Health education was delivered by lecture and question and answer methods and held on 15 August 2018 at Bunnaya ICBB PAUD Yogyakarta. It was attended by 55 participants. The material includes: definitions, characteristics, influencing factors, ways of stimulation and how to detect children’s growth and development. Conclusion: Participants understood about counseling materials and would carry out stimulation and early detection activities of growth and development directly to their children.